An Indonesian Teacher's Strategies for Preparing Students' Debate Teams for Competition - Mobit; Muhammad Hafidh Fadlillah; Yousef Bani Ahmad (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2022)
In an ELT environment, English debate is a good extracurricular activity. As a result, it is becoming a noteworthy event in school or university. The goal of this study is to investigate an English teacher's debate teaching approach in an Indonesian high school. The training method utilized was crucial since it improved students' understanding of the knowledge acquisition process (Wegner e. al., 2013). Observation, interviewing, and documenting were used to obtain data, which was then reviewed qualitatively using a case study technique. The findings revealed that the instructor used successful teaching strategies to help the students' debate team win the competition. Regular debate practice, brainstorming, using the 3M concept, and encouraging students were among the teacher's training strategies. Meanwhile, the students' reaction has been positive.